Learning activity content as a social factor of developing teenagers’ creativity - Babii, Mukola (Psychological Prospects Journal, 2014)
Babii M. F. Learning Activity Content as a Social Factor of Developing Teenagers’ Creativity. The process of studying is the key factor of developing the human creative abilities. The creative activity requires the introduction of active forms and methods of teaching into the academic process. They can provide the forming of divergent thinking, imagination of students. The originality and individuaality are specific while acquiring new knowledge through their combination, construction, and development of individual creativeness by a teenager. The goal of the learning activity is the forming of scientific knowledge. Therefore, the present paper is focused on how the content of lessons influences the development of teenagers’ creative abilities. Among the participants of the empirical study were the students of middle schools who specialized in mathematics and philology. It has been defined that while studying natural sciences the students are demonstrating more originality and flexibility. Thus, it has been found out that the content of learning activity determines the degree of teenagers’ creativity. Keywords: creativity, thinking, learning activities, originality, individuality, flexibility.